2013
DOI: 10.1016/j.adolescence.2013.03.012
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ‘theory of mind’ and attachment‐related anxiety and avoidance in Italian adolescents

Abstract: This study examined the relationship between ‘theory of mind’ and attachment‐related anxiety and avoidance in adolescence. The “Reading the Mind in the Eyes” test and the “Experiences in Close Relationships – Relationship Structures” questionnaires were administered to 402 14–19 year‐old adolescents. Contrary to expectations, anxiety but not avoidance with mother was associated with less accurate mindreading, and this effect was stronger in younger than in older adolescents. Results might be explained in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 27 publications
6
29
1
4
Order By: Relevance
“…Behavioral studies showed that mentalizing ability in childhood is influenced by attachment security to mother (Fonagy et al, 1997;Meins et al, 1998;Symons and Clark, 2000;De Rosnay and Harris, 2002) and to father (Fonagy et al, 2007) and that affective mentalizing ability in adolescence is modulated by AAS (Huenefeldt et al, 2013b). The relation of AAS and affective mentalizing in adulthood was investigated in healthy women in a behavioral study using a paradigm with stimuli from the eye region (''Reading the mind in the eyes test'' = RMET) and a two-dimensional self-report measure of AAS (''Experiences in Close Relationships'' questionnaire) (Huenefeldt et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies showed that mentalizing ability in childhood is influenced by attachment security to mother (Fonagy et al, 1997;Meins et al, 1998;Symons and Clark, 2000;De Rosnay and Harris, 2002) and to father (Fonagy et al, 2007) and that affective mentalizing ability in adolescence is modulated by AAS (Huenefeldt et al, 2013b). The relation of AAS and affective mentalizing in adulthood was investigated in healthy women in a behavioral study using a paradigm with stimuli from the eye region (''Reading the mind in the eyes test'' = RMET) and a two-dimensional self-report measure of AAS (''Experiences in Close Relationships'' questionnaire) (Huenefeldt et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Su dalimi šių rezultatų dera ir keleto kitų tyrimų, kuriais nustatytas ryšys tarp motinos numanymo apie vaiko psichiką ir ketverių metų vaikų PT (Meins, Fernyhough, Arnott, Leekam, & De Rosnay, 2013), atskleistos sąsajos su skirtingais vaikų PT ypatumais (Laranjo et al, 2010), radiniai. Reikia paminėti, kad motinos numanymo apie vaiko psichiką prognostiškumas vaiko PT nėra patvirtinamas, kai tai koduojama struktūruotose mamos ir vaiko sąveikose (Ereky-Stevens, 2008) arba kai vaiko PT vertinama iki ketverių metų amžiaus (Dore & Lillard, 2014).…”
Section: Mentalizacijos Raidos Veiksniai Ankstyvojoje Vaikystėjeunclassified
“…Kitame tyrime (Venta & Sharp, 2015) prieraišumo strategijų analizė parodė, kad vengiantį, nerimastingą ir saugų prieraišumą turinčių paauglių mentalizacija yra panašaus lygio, tačiau skiriasi nuo dezorganizuotą prieraišumą turinčių paauglių, kurių mentalizacija prastesnė. Dar vienas tyrimas, kuriame analizuotos su prieraišumu susijusio vengimo ir nerimastingumo ir PT sąsajos, atskleidė, kad paauglystėje, o ypač jaunesniojoje, tik nerimastingas, bet ne vengiantis prieraišumas buvo neigiamai susijęs su mentalizacijos tikslumu (Hünefeldt et al, 2013). Autoriai, aptardami keletą interpretacijų, kaip vieną iš, ko gero, realistiškiausių paaiškinimų pateikia prielaidą, kad galbūt abu reiškiniai priklauso nuo trečiojo -motinos nenuoseklumo, kuris laikomas nerimastingo prieraišumo veiksniu, kartu komplikuoja ir PT įgijimą.…”
Section: Tėvų Mentalizacijos Ir Vaiko Prieraišumo Sąsaja Su Mentalizaunclassified
See 2 more Smart Citations